Effect of processing on the phenolic contents, antioxidant activity and volatile compounds of sorghum grain tea - Xiong, Y.; Zhang, P.; Luo, J.; Johnson, Stuart; Fang, Z. (Academic Press, 2019)
Sorghum grain is rich in phenolic compounds and may be used to develop functional tea beverages. This work investigated the effect of processing techniques on the phenolic contents, antioxidant activity, and volatile compounds of a white colour sorghum (Liberty) grain tea. Significant (P = 0.05) increase of total phenolic content, total flavonoid content and condensed tannin content were observed during the processing, whereas the antioxidant activity was not statistically enhanced. A total of 63 volatile compounds were detected including 5 alcohols, 13 alkanes, 2 aldehydes, 2 carboxylic acids, 15 esters, 4 ketones, 3 pyrazines and 1 phenylenediamine, which were affected by the processing techniques. The sorghum tea made from powder form infusion had more abundant volatile compounds compared to whole grain form infusion. The findings of this research have potential to expand human consumption of sorghum grain in the new form of grain tea.